The influence of safety management practices towards safety performance among insured person in commuting accident - Mohammed Azman, Aziz Mohammed (2015)
Safety performance play the crucial role in safety management development at the workplace. It’s also contribute the main indicator to the success of accident prevention programme. This study purposely to examine the relationship between safety performance with safety management practise. Theory plan behaviour was applied to develop conceptual framework. In this study safety management practise was independent variable and safety performance was dependent variable. While the safety motivation and employees’ competency were mediating variable. Quantitative approach was applied in methodology of this study which involved 615 respondents among insured employees who involved in commuting accident.Regression analysis revealed that safety management practise, safety motivation, and employees’ competency have positive relationship significantly with safety performance. Safety motivation and employees’ competency was found mediated the relationship between safety management practice and safety performance. This study highlighted the organisation should give priority to improve their safety accident prevention programme by enhance employees’ knowledge, skills and abilities. In addition, employees; characteristics should be taken into account during the development of safety training need analysis.